Abdominal ectopic pregnancy: a report of two cases - Elías Estrada, José Carlos (2021)
We present two cases of abdominal ectopic pregnancy of 16 and 26 weeks, evaluated with ultrasound and magnetic resonance imaging. Both cases presented an acute surgical abdomen, the case with the oldest gestational age showed hemodynamic decompensation due to hemoperitoneum secondary to placental abruption. The clinical presentation led to resolution by laparotomy and extraction of the fetus and placental tissue, ending in hysterectomy due to trophoblastic involvement of the uterine surface and adjacent organs in the first case. The 26-week-neonate died after 4 months due to late sepsis. Clinical suspicion for amenorrhea and severe abdominal pain are important criteria, and imaging studies, especially ultrasound, are the main diagnostic tools.